Effect of heat treatment on the width of the forbidden band of polyoxide films formed on the surface of tool steel; Metal Science and Heat Treatment; Vol. 44, № 7-8 - Nesterenko V. P.; Arefyev (Afef'ev, Arefiev) K. P. Konstantin Petrovich; Merkulov V. I.; Kondratyuk A. A.; Serikov L. V. (2002, 2002)
The process of formation of polyoxide films on the surface of high-speed steel after high-temperature heating is studied. The relation between the modes of heat treatment of the tool steel and the width of the forbidden band of polyoxide films is obtained.